Effect of Land Fragmentation and Socioeconomic Factors on Food Crop Productivity in Ogun State, Nigeria - Oyebanjo, Olumayowa (EuroEconomica, 2023)
Land fragmentation has been considered as a source of low productivity with high production costs resulting from scattered farm plots. This study examined the implication of land fragmentation on food crop productivity. Primary data were collected from 118 farmers through a multistage and snowball sampling techniques using structured questionnaire. Descriptive statistics, land fragmentation indices and Cobb-Douglas production function were used in data analyses. Descriptive results show that an average farmer was 51.7 years old, 61.0% was male, and 75.4% was married with average of 5 persons within household while 87.3% had formal education. About 86.4% derived major income from farming, average farmer cultivated 3.82 ha with 19 years of experience. Majority (57.6%) of the farms was acquired through inheritance, 24.6% rented/borrowed, 17.8% purchased (17.8) while 69.5% operated two (2) or more parcels. Productivity was promoted by Age (0.471) and education (0.261) at p<0.01 while it was reduced by land fragmentation (-0.323) and distance from homestead to farm locations (-0.324) at p<0.05 and p<0.01 respectively. Therefore, cooperative farming should be promoted with subsidized inputs to enhance farm mechanization and productivity. Land consolidation policy should be used to partially restrict total land inheritance in order to reduce land fragmentation in the area.